BS EN 15316-4-2. Energy performance of buildings. Method for calculation of system energy requirements and system efficiencies. Part 4-2. Space heating generation systems, heat pump systems, Module M3-8-2, M8-8-2 (3rd March 2022) - British Standards Institution,
No abstract available